ANALISIS TRANSPARANSI TERHADAP LAPORAN KEUANGAN PADA KANTOR DESA GOARIE KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - Irwandi, Syahrul; Iskandar, Sultan; Paweroi, Arsyad; Tibola, Jordan (Universitas Patria Artha, 2024)
This study aimed to determine the effect of transparency on financial reports at the Goarie village office, Marioriwawo sub-district, Soppeng Regency. The method used in this research is a descriptive method with a quantitative approach by determining the primary data from the questionnaire. The population in this study was all village officials, totaling 30 people. The data collection techniques used in this study were observation, questionnaires, and documentation. Data analysis techniques were used: validity test, reliability test, simple linear regression analysis, hypothesis test, and adjusted coefficient of determination with the help of the SPSS program. The results of the study showed that transparency had a positive effect on financial reports in the Goarie village office, Marioriwawo sub- district, Soppeng Regency